The Implementation of Benford's Law to Detect Indications of Corruption Patterns in Government Institutions - Restianto, Yanuar E.; Sudibyo, Yudha Aryo; Qosasi, Achsanul; Suwarno, Suwarno (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
Disclosure of corruption cases requires a collaboration of experts in law, accounting, and auditing. In Indonesia's context, corruption patterns in government institutions can be identified based on the types of expenditure and the timing of cash disbursements. This study aims to reveal the indications and patterns of corruption in Indonesian government institutions. This study uses data on cash disbursements to detect indications and patterns of corruption. The first-digit, second-digits and first-two-digits digital analysis methods based on Benford's law were employed to analyze the data. This study found differences in cash disbursement transactions data value and Benford's law value. Furthermore, this study also discovers that corruption in government institutions follows a pattern in which corruptions often occur in the procurement of goods/services, purchases of food and beverage, and miscellaneous payments. The indications of corruption transpire throughout the year and show an increase at the end of the year (i.e., October to December), suggesting a 'year-end rush' and a phenomenon of 'hurry-up spending' in government institutions. Another pattern is related to digit groups of 30, 50, 60, and 90 committing corruption through cash disbursement transactions deliberately.